Steinepigramme aus dem griechischen Osten (Stuttgart München München München)
5 c. (1. c. xv, 647 s. ; 2. c. xii, 399 s., 2 s. harita ; 3. c. xii, 416 s., [4] s. harita ; 4. c. xvi, 471 s., [2] s. harita ; 5. c. ix, 341 s.)